Unsur Komunikasi Pada Pelayanan Perpustakaan (Studi Kasus Di Perpustakaan SMP Negeri 3 Rantau Bayur) - Tridana, Anggi; Misroni, Misroni (Jurnal Tadwin, 2023)
This article aims to identify and analyze the communication elements involved in library services at SMPN 3 Rantau Bayur, and to explore how effective communication can enhance the quality of library services and user satisfaction. To gain a deeper understanding of these communication elements, the author explains their role within the context of library services at SMPN 3 Rantau Bayur. This study employs a qualitative descriptive approach, utilizing observations and interviews conducted by the author. The conclusions are drawn using inductive data analysis, which helps to build hypotheses or theories based on the observed facts. The study's findings indicate that the elements of communicator, message, medium, communicant, and effect are the primary components influencing communication in library services. These five elements are interrelated and mutually influence one another, forming a cohesive whole. By recognizing and understanding these various elements in the context of library service communication at SMPN 3 Rantau Bayur, it is possible to achieve high-quality library services and ensure satisfaction for all stakeholders within the school community.